‘[La casa] non è più sexy in Italia.’ The absent politicization of housing in Italy, insights from Turin - Tulumello, Simone (2021)
During the years of economic crisis and austerity, and the subsequent economic growth dependent on real estate and tourism, housing has returned into the spotlight on the political agenda in Southern European countries and cities, where activists and social movements scaled up their struggles and created bridges with institutional actors, fostering policy change. The latter, however, did not happen in Italy. In this article, based on exploratory case study research carried out in the city of Turin, we present three themes that help explain what we call the ‘absent politicization’ of housing in Italy during the last decade: a multi-actor, multilevel housing policy capable of defusing specific problems; the absence of bridges between politicized and institutional actors; and the role played by party-politics, with attention to ‘populist’ Movimento 5 Stelle in power in Turin. By focusing on differences with Southern Europe, we contribute to overcoming dichotomies that have long dominated comparative housing studies; and contribute to linking housing studies with contentious urban politics in the post-crisis years.